2015
DOI: 10.1093/jme/tjv059
|View full text |Cite
|
Sign up to set email alerts
|

Venom allergen 5is Associated With Deltamethrin Resistance inCulex pipiens pallens(Diptera: Culicidae)

Abstract: The mosquito, Culex pipiens pallens (L.), is an important vector of encephalitis and filariasis in northern China. The control of these mosquitoes occurs primarily via the use of pyrethroid insecticides, such as deltamethrin. The widespread and improper application of pyrethroid has resulted in the evolution of pyrethroid resistance amongst many mosquito populations, including Cx. pipiens pallens. Previous studies using high-throughput transcriptome sequencing have identified that the venom allergen 5 gene is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…pipiens. Other genes found to be expressed in males, thereby showing a consistency with other studies include tetraspanin F139 (Boes et al, 2014) in adults and venom allergen 3 in pupae (Lv et al, 2015). A C-type lectin expressed in male adults in this study, however, was previously found to be associated with females (Adelman and Myles, 2018).…”
Section: Qrt-pcr Validation Of Sex-specific Genessupporting
confidence: 91%
See 1 more Smart Citation
“…pipiens. Other genes found to be expressed in males, thereby showing a consistency with other studies include tetraspanin F139 (Boes et al, 2014) in adults and venom allergen 3 in pupae (Lv et al, 2015). A C-type lectin expressed in male adults in this study, however, was previously found to be associated with females (Adelman and Myles, 2018).…”
Section: Qrt-pcr Validation Of Sex-specific Genessupporting
confidence: 91%
“…The genes involved in microtubule-based process have been associated with mosquito sperm composition (Degner et al, 2019), which suggests the possibility that the tubulin and associate proteins are involved in the spermatogenesis process and play an important function in late male pupae and early male adults. The genes encoding allergen are also present, including venom allergen 5, in male pupae, which are most likely associated with insecticide resistance (Lv et al, 2015). The four genes encoding calcium ion binding proteins in male pupae are also consistent with the findings that calcium-dependent regulation is necessary for normal sperm motility (Degner and Harrington, 2016).…”
Section: David Analysis Of Functional Annotation Clusteringsupporting
confidence: 65%
“…() identified a cluster of carboxylesterase genes (CCE) determining resistance to the organophosphate temephos within the major QTL interval. In Culex , previous studies mainly focused on the association between one or a few genes and pyrethroids resistance (Li et al ., ; Fang et al ., ; Lv et al ., ; Gong et al ., ). This study provides the first evidence of candidate major genes potentially related to DM resistance in C. pipiens by DR‐6.…”
Section: Resultsmentioning
confidence: 99%
“…Mosquito mortality was analyzed using the Chi-square test [36,37]. Other experimental data were analyzed using the Student's t-test.…”
Section: Discussionmentioning
confidence: 99%